Respuesta :

Answer:

hopes this helps!

Step-by-step explanation:

1) −y−9z=4−10x

2 Add 9z9z to both sides.

-y=4-10x+9z

−y=4−10x+9z

3 Multiply both sides by -1−1.

y=-4+10x-9z

y=−4+10x−9z

2)1 Add 4x4x to both sides.

y+4z=-1+4x

y+4z=−1+4x

2 Regroup terms.

y+4z=4x-1

y+4z=4x−1

3 Subtract 4z4z from both sides.

y=4x-1-4z

y=4x−1−4z

3)1 Add yy to both sides.

-x+z=6+y

−x+z=6+y

2 Regroup terms.

z-x=6+y

z−x=6+y

3 Subtract zz from both sides.

-x=6+y-z

−x=6+y−z

4 Multiply both sides by -1−1.

x=-6-y+z

x=−6−y+z